2022
DOI: 10.1097/md.0000000000029783
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of real-world treatment outcomes of small cell lung cancer

Abstract: Background: Robust evidence from real-world studies is needed to aid decision-makers and other stakeholders in choosing the best treatment options for patients. The objective of this work was to assess real-world outcomes of treatment strategies for limited-and extensive-stage small cell lung cancer (SCLC) prior to the global introduction of immunotherapies for this disease.Methods: Searches were conducted in MEDLINE and Embase to identify articles published in English from October 1, 2015, through May 20, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Our results yielded an AUC of 0.784, showing moderate predictive power. The prognosis of different histopathological subtypes varies greatly, and patients with SCLC usually have a poor prognosis (33). Moreover, the clinical TNM stage is another important prognostic factor for patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our results yielded an AUC of 0.784, showing moderate predictive power. The prognosis of different histopathological subtypes varies greatly, and patients with SCLC usually have a poor prognosis (33). Moreover, the clinical TNM stage is another important prognostic factor for patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis by Stokes et al [ 74 ] was published with the aim of assessing the outcomes of treatment strategies for limited- and extensive-stage SCLC by analyzing studies published between 2015 and 2020. In the group of limited-stage disease (including patients with stage I to III), the proportion undergoing surgery was 4.2 to 10.8%; nearly all studies demonstrated significant survival benefits favoring treatment approaches including surgery; however, no significant improvement in OS following surgery was seen in patients with stage II–III SCLC, confirming the leading role of surgical therapy only in patients with early-stage tumors.…”
Section: High-grade Nets: Is There a Role For Surgery?mentioning
confidence: 99%
“…As a life-threatening non-communicable disease, cancer severely affects the quality of patient's life and puts a severe burden on healthcare systems [ 3 , 4 ]. Among all types of cancers, the lung cancer is the most frequently diagnosed one (∼2 million new cases/year) and accounts for almost 20% of all cancer deaths [ 5 , 6 ]. Research driven towards understanding the cancer biology has led to the discovery of novel targets and novel therapies for treatment of cancer [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%